2011
DOI: 10.1017/s0007114511000559
|View full text |Cite
|
Sign up to set email alerts
|

Faecal IgA concentration is influenced by age in dogs

Abstract: Data comparing age-related alterations in faecal IgA concentrations of dogs are not available in the literature. The present study aimed to compare the faecal concentrations of IgA in puppies, mature and senior dogs. A total of twenty-four beagle dogs were used, including eight puppies (5 months old, four females and four males), eight mature (4·6 years old, eight males) and eight senior dogs (10·6 years old, three males and five females). Fresh faecal samples were collected from each dog for three consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
3
18
1
3
Order By: Relevance
“…In previous studies other authors reported that concentration of the fecal IgA was lower in 5-month-old puppies compared to 4-year-old adults [24], which was also found in the present study. However, in the present study the puppies were aged 7 weeks only.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In previous studies other authors reported that concentration of the fecal IgA was lower in 5-month-old puppies compared to 4-year-old adults [24], which was also found in the present study. However, in the present study the puppies were aged 7 weeks only.…”
Section: Discussionsupporting
confidence: 91%
“…IgA is the most abundant class of antibody in mucous membranes, where it is an essential factor in protecting against infectious agents, allergens and foreign proteins [24] and has a concentration which could be affected by stress. It has been found that levels of sIgA in adult dogs decreased following long-term stress [25] and an acute stress [26].…”
Section: Introductionmentioning
confidence: 99%
“…Immunoglobulin A (IgA) is the most abundant antibody in mucous membranes, where it has a protective role against infectious agents, allergens and foreign proteins [116]. IgA has been described as a stress biomarker in rats [117], dogs [118] and humans [119].…”
Section: Biomarkers Of Stress Studied In Pigsmentioning
confidence: 99%
“…The method used for saline extraction of fecal Ig was adapted from that used by Peters et al (2004) and Zaine et al (2011). The frozen fecal samples were thawed at room temperature, and mixed samples were composed of an equivalent quantity of feces from the same individual.…”
Section: Extraction Of Fecal Ig and Cortisolmentioning
confidence: 99%